Advances of Coagulation Factor XIII - Shi, Da-Yu (Chin Med J (Engl), 2017)
OBJECTIVE: To provide a comprehensive literature review on roles of coagulation factor XIII (FXIII) in coagulation, wound healing, neoplasm, bone metabolism, and pregnancy. DATA SOURCES: All articles in PubMed with key words Coagulation factor XIII, wound, leukemia, tumor, bone, and pregnancy with published date from 2001 to 2016 were included in the study. Frequently cited publications before 2000 were also included. STUDY SELECTION: We reviewed the role of FXIII in biologic processes as documented in clinical, animal, and in vitro studies. RESULTS: FXIII, a member of the transglutaminase (TG) family, plays key roles in various biological processes. Besides its well-known function in coagulation, the cross-linking of small molecules catalyzed by FXIII has been found in studies to help promote wound healing, improve bone metabolism, and prevent miscarriages. The study has also shown that FXIII concentration level differs in the blood of patients with leukemia and solid tumors and offers promises as a diagnostic indicator. CONCLUSIONS: FXIII has many more biologic functions besides being known as coagulation factor. The TG activity of FXIII contributes to several processes, including wound healing, bone extracellular matrix stabilization, and the interaction between embryo and decidua of uterus. Further research is needed to elucidate the link between FXIII and leukemia and solid tumors.